Influence of Role Ambiguity and Conflicts on the Independence Commitment of Internal Auditor - W. Lamidi; M. Oyekanmi; T. Kareem (Хабаршысы. Экономика сериясы, 2021)
To increase the credibility of financial statements, an audit must provide documented reasonable assurance from an independent source that the financial statements provide a true and fair picture in compliance with an accounting standard. Independence is the freedom from circumstances which may lead to impartial conduct of the internal auditing functions. To maintain independence, auditors must ensure integrity and take an objective approach to the audit process. The auditor is required to carry out his or her task in a free and objective manner in accordance with the notion. The objective of this study is to examine the influence of role ambiguity and conflict on the independence commitment of internal auditors of tertiary institutions in Osun State, Nigeria. The study population consists of the internal auditors of tertiary institutions in Osun State. The study selected sixty (60) internal auditors from the state-owned tertiary institutions to respond to the survey, using purposive sampling techniques. Multiple regression was conducted to analyse the data obtained. The study showed that role ambiguity and role conflict had a negative influence on the commitment of internal auditors to independence. The findings demonstrate, however, that the study’s projections are statistically validated. The results of this study would provide empirical support for the reasons behind the resistant to independence commitment among internal auditors. Key words: Internal auditors, Independence commitment, Role ambiguity, Role conflict.